Influence of salinity on the development of six forage species in two implementation techniques, lower basin of the Lauca River - Paco-Pérez Víctor; Choque-Marca Willy (Journal of the Selva Andina Biosphere, 2020)
The accumulation of soluble salts in the root zone of plants greatly limits the production of fodder in many parts of the world. The objective of this study was to assess the influence of salinity on the development of forage species among planting and transplantation techniques. The research was carried out 204 kilometers from the city of Oruro, Bolivia, specifically in the lower Lauca river basin of the territory of Uru Chipaya at 3640 altitude msnm, geographically between the coordinates 19°0217,40 Latitude Sud and 68°0516,05 West Longitude; average annual temperature of 10.4 °C, precipitation from 200 to 4000 mm, relative humidity 70%. Six forage species were used: mouse tail (Hordeum muticum J. Presl), cebadilla INTA (Bromus sp.), native cebadilla (bromus catharticus Vahl.), tall fescue (Festuca arundinacea Schreber), alkar (Agropyron elongatum (Host) P. Beauv.) and weeping grass (Eragrostis curvula (Schrad.) Nees). The variables evaluated were: emergence, mortality, plant height (PH), number of macules (NM) and dry matter (DM). A randomized full block experimental design was used with four repetitions per species. In transplant they presented high significance among the species, and had a better behavior than the sowing technique, the PH, NM and DM were superior and the mortality was minimal in all, B. catharticus Vahl in 7 dS m-1 presented the highest biomass with 166.00 kg DM ha-1, but at 16 and 22 dS m-1 it was gradually affected that only reached 161.33 and 151.33 kg DM ha-1 respectively. In the sowing the mentioned variables also presented significant differences, but they were lower than the transplant; the species of the transplant that showed better biomass in 7 and 16 dS m-1, was the same that presented bigger biomass of 109.33 and 107.67 kg DM ha-1 respectively, but at 22 dS m-1 they did not manage to emerge any species. It is concluded, high levels of salinity affect negatively on the germination, emergence and development of the seedlings, with a higher degree in sowing than in transplanting. The best option to implement forage species in saline soils is through the technique of seedling transplantation.